Effect of Material Composition on Thermal Stability Analysis of Coated and Uncoated FeCrAl CATCO by Î³-Al2O3 Ultrasonic-Electroplating Technique - Feriyanto, Dafit; Abdul Malik, Samir Sani; Fitri, Muhamad; Hidayat, Imam; Pranoto, Hadi; Zakaria, Supaat (Journal of Sustainable Materials Processing and Management, 2021)
Catalytic converter (CATCO) material become an interesting field to investigate due to the common CATCO material being ceramic material that has high brittleness than metallic materials. Therefore, this research investigates the FeCrAl metallic material as CATCO substrate that is coated by Î³-Al2O3 as a washcoat, Nickel oxide (NiO) as a catalyst. The coating analysis was performed by ultrasonic using a frequency of 35 kHz and various ultrasonic times of 1, 1.5, 2, 2.5, and 3 hours and electroplating technique by sulphamate types electrolyte using variation times of 15, 30, 45, 60, and 75 minutes, a current density of 8 A/dm2. The result shows that the raw material was consists of Fe, Cr and Al with Fe element was dominated for 74.13wt%. Coated sample by ultrasonic consists of Fe, Cr, Al, O, and C elements due to FeCrAl substrate was deposited by Î³-Al2O3 powder and by electroplating technique consists of Fe, Cr, Al, O, C, Ni and Na elements due to NiO deposition as catalyst material. TGA analysis observed that the highest mass change was observed by raw material 23.39 mg and UB+EL 30 min samples for lowest mass change of 2.85 mg with a point of the reaction is 0.07 mg/min may be caused by a protective oxide layer that developed during the coating process. Therefore, the coated metallic CATCO has a promising prospect to replace the ceramic CATCO due to high thermal stability by protecting layer and low mass change.